The Relationship Between Personality Traits and the Strategies of Coping withlevels of Perceived Stress in Nurses - M NadiRavandi; F SedighArfaei; M Barbari (Iran University of Medical Sciences, 2015)
Abstract Background & Aim: The nursing profession is considered as a major source of stress by itself. Several factors are helpful in reducing the effects of stressful situations which include strategies of coping with stress and fitting personality traits. The main objective of this study is to investigate the relationship between personality traits and strategies of coping with levels of perceived stress of nurses . Material & Methods: This research is a descriptive-correlational study. The population of this study wereall nurses in Shahid Beheshti Hospital, which by means of Krejcie & Morgan table, 127 nurses were selected as the sample. The instruments of this study were the NEO five-factor personality inventory, coping inventory for stressful situations by Endler and Parker and stress symptoms test. Data analysis was carried out using inferential statistics (Pearson correlation and analysis of variance) with SPSS 19. Results: Results showed that there is a significant positive correlation between neuroticism and emotion-oriented coping, between extroversion witht ask-oriented and avoidance-oriented coping and also between agreeableness and conscientiousness traitswith task-oriented coping (p<0.01). There is a significant positive relationship between neuroticism and cognitive perceived stress (p<0.05). A significant negative correlation exists between extroversion and behavioral symptoms, between openness to experience and emotional and behavioral perceived stress, between conscientiousness with physical and behavioral perceived stress. Among the variables, only the emotion-oriented coping has a significant positive correlation with perceived stress (p<0.01). Conclusion: Employing nurses with protective personality traitsand identifying nurses at risk and the use of therapeutic interventions such as teaching skills of coping with mental pressure and strengthening protective personality factors can be helpful in preventing nurses from stress and burn out.